Developing a Computational Educational Game “Math Squirrel” to Improve the Learning Motivation of 6th Grade Elementary School Students - Hasanah, Huswatun; Abadi, Ma'ulfi Kharis; Yanuar, Melinda; Darmawan, Rivaldi; Gandhi, Herry Kartika (Kreano, Jurnal Matematika Kreatif-Inovatif, 2025)
Educational games hold substantial potential to create enjoyable and meaningful learning experiences for students. In today’s educational landscape, one of the main challenges is maintaining students’ interest and motivation, especially amid the rapid advancement of technology and the pervasive influence of digital entertainment. By integrating interactive and engaging elements, educational games can foster learning environments that are both motivating and enjoyable. This study aimed to demonstrate that the computational educational game Math Squirrel is a valid, practical, and effective learning medium for enhancing the learning motivation of sixth-grade elementary school students in mathematics. Developed using the Unity engine and based on the 4D development model, the game underwent validation by subject matter and media experts, yielding average scores of 94.44% and 83.92%, respectively—indicating a high level of feasibility. A trial involving 30 students at SDN 1 Cipocok Jaya resulted in a positive response rate of 87.08%. During gameplay-based learning sessions, students appeared highly engaged, enthusiastic, and actively involved in solving problems embedded in the game. The interactive challenges, colorful visuals, and immediate feedback contributed to a fun and stimulating learning atmosphere. This study concluded that Math Squirrel computational educational game is a valid, practical, and effective tool for increasing the learning motivation of sixth-grade elementary students in mathematics. These findings suggest that Math Squirrel not only enhances learning motivation but also provides an engaging and joyful educational experience, making it a highly feasible and innovative tool for improving student motivation in elementary mathematics instruction. Abstrak Permainan edukatif memiliki potensi besar dalam menciptakan pengalaman belajar yang menyenangkan dan bermakna bagi siswa. Dalam lanskap pendidikan saat ini, salah satu tantangan utama adalah mempertahankan minat dan motivasi belajar siswa, terutama di tengah pesatnya kemajuan teknologi dan pengaruh hiburan digital yang meluas. Dengan mengintegrasikan elemen interaktif dan menarik, permainan edukatif dapat membangun lingkungan belajar yang memotivasi dan menyenangkan. Penelitian ini bertujuan untuk menunjukkan bahwa game edukasi berbasis komputer Math Squirrel merupakan media pembelajaran yang valid, praktis, dan efektif untuk meningkatkan motivasi belajar matematika siswa kelas enam sekolah dasar. Game ini dikembangkan menggunakan mesin Unity dan model pengembangan 4D, serta divalidasi oleh ahli materi dan media dengan skor rata-rata masing-masing sebesar 94,44% dan 83,92% yang menunjukkan tingkat kelayakan yang tinggi. Uji coba terhadap 30 siswa di SDN 1 Cipocok Jaya menunjukkan respons positif sebesar 87,08%. Selama sesi pembelajaran berbasis permainan, siswa tampak sangat antusias, terlibat aktif, dan termotivasi menyelesaikan soal-soal yang disajikan dalam permainan. Tantangan interaktif, visual yang berwarna-warni, dan umpan balik langsung menciptakan suasana belajar yang menyenangkan dan merangsang. Penelitian ini menyimpulkan bahwa game edukatif Math Squirrel merupakan media pembelajaran yang valid, praktis, dan efektif dalam meningkatkan motivasi belajar matematika siswa kelas enam sekolah dasar. Temuan ini menunjukkan bahwa Math Squirrel tidak hanya meningkatkan motivasi belajar, tetapi juga memberikan pengalaman pendidikan yang menyenangkan dan inovatif, sehingga sangat layak digunakan sebagai alat bantu pembelajaran untuk meningkatkan motivasi siswa dalam pembelajaran matematika di sekolah dasar.